1999 Philippine Talent Search for Young Scientists (PTSYS) award - Tolentino, Elaine (Animo Repository, 1999)
Dr. Elaine Tolentino of the Physics Department, placed third in the 1999 Philippine Talent Search for Young Scientists (PTSYS) Award among 16 qualified candidates from all over the country. Tolentino presented her research, Effects of Cu2+ Ions on the Structure and Reactivity of Todorokite-and Hollandite-Type Manganese Seives (OMS) to a NAST panel in March, 1999.